DEVELOPMENT OF YOUTUBE-BASED DEBATE VIDEO LEARNING MEDIA FOR DEBATE TEXT SPEAKING SKILLS FOR CLASS XI STUDENTS OF STATE HIGH SCHOOL 2 TANJUNGPINANG CITY FOR THE 2022/2023 ACADEMIC YEAR : Pengembangan Media Pembelajaran Video debat Berbasis Youtube Untuk Pemahaman Teks Debat Siswa Kelas XI SMA Negeri 2 Kota Tanjungpinang Tahun Pelajaran 2022/2023 - Nurayuni; Abdul Malik; Legi Elfitra (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Abstract This research aims to develop a YouTube-based Debate Video learning media for Debate Text Speaking Skills for Class Xi Students of State High School 2 Tanjungpinang City for the 2022/2023 Academic Year. This research uses a 4D development model up to the development stage. The product developed in this research is audio-visual based learning media using the Kinemaster, Canva and Capcut applications. This learning media has been assessed based on the assessments of two experts, namely media experts and material experts. The number of students in this media trial was 5 students for the small group and 40 students for the large group. Data collection techniques in this research are interviews, media validation questionnaires by media experts and material experts, and media practicality questionnaires by students. The data analysis technique in this research was carried out using two techniques, namely descriptive qualitative and descriptive quantitative. The results of this research obtained an average of 91,25% with the criteria